Novel compound heterozygous variants of SLC12A3 gene in a Chinese patient with Gitelman syndrome: a case report - Chen, Wenqing; Zhou, Qin; Chen, Hongjun; Li, Heng; Chen, Jianghua (Frontiers in Genetics, 2023)
Background: The Gitelman syndrome (GS) is an autosomal recessive disorder of renal tubular salt handling. Gitelman syndrome is characterized by hypokalemia, metabolic alkalosis, hypomagnesemia, hypocalciuria, and renin-angiotensin-aldosterone system (RAAS) activation, and is caused by variants in the SLC12A3 gene. Gitelman syndrome has a heterogeneous phenotype, which may or may not include a range of clinical signs, posing certain difficulties for clinical diagnosis. Case presentation: A 49-year-old man was admitted to our hospital due to muscular weakness. The patient’s history revealed previous recurrent muscular weakness events associated with hypokalemia, featured by a minimum serum potassium value of 2.3 mmol/L. The reported male patient had persistent hypokalemia, hypocalciuria and normal blood pressure, without presenting obvious metabolic alkalosis, growth retardation, hypomagnesemia, hypochloremia or RAAS activation. We performed whole-exome sequencing and identified a novel compound heterozygous variant in the SLC12A3 gene, c.965-1_976delGCGGACATTTTTGinsACCGAAAATTTT in exon8 and c.1112T>C in exon9 in the proband. Conclusion: This is a study to report a heterogeneous phenotype Gitelman syndrome with a novel pathogenic compound heterozygous variant in the SLC12A3 gene. This genetic study expands the variants spectrum, and improve the diagnostic accuracy of Gitelman syndrome. Meanwhile, further functional studies are required to investigate the pathophysiological mechanisms of Gitelman syndrome.